FAKTOR – FAKTOR YANG MEMPENGARUHI PENERIMAAN INTERNET SEBAGAI ALAT PENDUKUNG TUGAS MAHASISWA - Ibnu Wibowo; Gandhi Pawitan; F Nugro Hardianto (Research Report - Humanities and Social Science, 2009)
Purpose – This paper aims to identify the importance that students attach to the internet as a tool of task support, and the factors that affect its acceptance as such a tool. Design/methodology/approach – Using the technology-acceptance model (TAM) as a basis, a questionnaire is designed by the researchers, and completed by students. Multiple linear regression is used to analyse the data, and this confirms the relationships proposed by the TAM. Findings – The main findings of the study are that: students feel that a task support system is a prerequisite for effectiveness in their work; they require greater access to the internet to meet their task support needs; perceived usefulness and perceived ease of use of the internet directly affect university students’ attitude – which, in turn, affect the students’ intentions of using the internet as a task support tool. Research limitations/implications – Main limitations of this study are related to the sampling method and the fact that the field research was conducted only in Bandung and Yogyakarta. Originality/value – Finally, the paper suggests how students could exploit the internet as a task support tool for students and what actions should be planned in order to facilitate its adoption.